2020
DOI: 10.1515/pp-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC)-directed treatment of peritoneal metastasis in end-stage colo-rectal cancer patients

Abstract: BackgroundPressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) represents a novel approach to intraperitoneal chemotherapy. Hereby results, obtained with PIPAC in patients with advanced peritoneal metastasis (PM) from colorectal cancer (CRC), are presented.MethodsData from CRC patients (n = 24) included in the prospective PIPAC-OPC1 and PIPAC-OPC2 trials are reported. Oxaliplatin 92 mg/m2 was administered at 4-6-week intervals. A CE certified nebulizer was used to aerosolize the chemotherapeutics. Outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 29 publications
0
14
1
5
Order By: Relevance
“…PIPAC has been suggested to be useful as palliative therapy for PM of recurrent or refractory solid tumors, which may lead to histologic regression, and thereby improve the quality of life (Tempfer et al., 2015 ; Horvath et al., 2018 ; Alyami et al., 2020 ; Ellebaek et al., 2020 ). Even if chemotherapeutic agents shown to be resistant in intravenous chemotherapy are used again in PIPAC, the agents may be absorbed into the peritoneal tumors by passive diffusion, which can be effective for treating PM by maintaining higher concentrations within tumor tissues while minimizing systemic absorption (Yan et al., 2010 ; Alyami et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…PIPAC has been suggested to be useful as palliative therapy for PM of recurrent or refractory solid tumors, which may lead to histologic regression, and thereby improve the quality of life (Tempfer et al., 2015 ; Horvath et al., 2018 ; Alyami et al., 2020 ; Ellebaek et al., 2020 ). Even if chemotherapeutic agents shown to be resistant in intravenous chemotherapy are used again in PIPAC, the agents may be absorbed into the peritoneal tumors by passive diffusion, which can be effective for treating PM by maintaining higher concentrations within tumor tissues while minimizing systemic absorption (Yan et al., 2010 ; Alyami et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Peritoneal Regression Grading Score (PRGS) was initially developed to quantify PM’s histological response to palliative intraperitoneal chemotherapy [ 8 ]. This study demonstrated that PRGS can also be used for measuring the objective response of PM to systemic, intravenous chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A generic, unique score for assessing histological tumor response to chemotherapy in PM makes sense because of the clinical impact of histological response to therapy and because the organ of metastasis (peritoneum) is the same [ 3 ]. The PRGS has been the object of a multi-institutional validation study [ 4 ] and is now diffusing into clinical practice [ 8 , 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ]. The PRGS is increasingly used as secondary [ 21 ], [ 22 ], [ 23 ], [ 24 ], or even as primary outcome criteria [ 25 ] in clinical studies on PM.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha reportado reducción significativa de ascitis, dolor, distensión abdominal y otros síntomas gastrointestinales 7 . En el tratamiento de metástasis peritoneales de origen colorrectal ha destacado la negativización de los estudios citológicos para células malignas, regresión tumoral y disminución de la ascitis y una mediana de sobrevida de 27,6 meses (10,2-47) 8 .…”
Section: Discussionunclassified